LITERATUR REVIEW: SUATU TINJAUAN FUNGSI AUDIT INTERNAL TERHADAP TATA KELOLA PERUSAHAAN - Permatasari , Septaria Salasi; Nugrahanti , Trinandari Prasetya (Publika Citra Media, 2024)
Along with increasingly rapid economic development, the role of internal audit in companies is becoming increasingly important, especially for corporate governance. The trend of globalization is intensifying, and trade between countries is increasingly dense. This brings economic benefits to the company while increasing risks. In order to survive and thrive, companies must face more challenges. On the one hand, enterprises should increase investment in internal governance management, and establish institutions such as shareholder meetings, boards of directors, manager levels and supervisory boards, and gradually standardize corporate governance structures. On the other hand, strengthening the company's internal audit can not only improve the company's operational conditions, but also discover problems within the company in a timely manner and control them effectively. However, compared to other developed countries in Indonesia, the internal audit system was established too late, so these units have different experiences in learning from abroad, thus causing many problems in establishing internal audit institutions in Indonesia, and many companies do not do so. pay attention to internal audits. The purpose of this research is to provide an overview of the relationship between the internal audit function and corporate governance in companies.